Techno-economic analysis for the comparison of biorefinery scenarios annexed to an existing South African sugarcane mill for the production of adipic acid - Cronje, Yakim (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.